El liberalismo económico “a la Argentina”. Discusiones políticas, 1875-1895 - Jimena CARAVACA è ricercatrice e docente universitaria. Frequenta un dottorato in cotutela tra la Universidad de Buenos Aires e quella di Paris 7; è inoltre membro del Comitato direttivo nell’Instituto de Desarrollo Económico. Ha pubblicato articoli sull’Argentina del periodo 1870-1930 e sul pensiero economico liberale nel paese latinoamericano (Diacronie. Studi di Storia Contemporanea, 2011)
The article explores the political discussions that took place in Argentina between 1870 and 1895 about the industrialization, development and the role of the State in these processes. Through the parliamentary debates, and contrasting these discussions with the academic content that was taught in the University, the article explores the peculiarities of the Argentine economic liberalism. It is argued that local economic practice combined -not explicitly -contents and arguments of the German Historicism with French liberal theory. The particular inclusion of the country in the international economic system and the attempt to prevent economic crises and to achieve development gave the economic liberalism of the time a particular label: “rational” protection of industries guided by an active State in the pursuit of growth.